Molecular identification of Sarcocystis species in diaphragm muscle tissue of European mouflon (Ovis gmelini musimon) from Austria - Prakas, Petras; Rehbein, Steffen; Rudaitytė-Lukošienė, Eglė; Butkauskas, Dalius (Parasitology research (1987), 2021)
Previous morphological studies suggested that mouflon may have sarcocysts similar to those of sheep. However, to date, no molecular-based studies of the species of Sarcocystis infecting mouflon have been done. The present study identified Sarcocystis species in diaphragm muscle samples from 20 European mouflon ( Ovis gmelini musimon ). Molecular identification using the cox1 sequence analysis was performed on sarcocysts excised from muscle tissue and on DNA from digested muscle samples. Both frequency and intensity of infection in mouflon were high with 19 of 20 animals testing Sarcocystis positive and > 50 cysts per gram of tissue recovered from 10 of the 19 Sarcocystis positive animals. Molecular analysis revealed dominant Sarcocystis tenella (18/19 animals) and Sarcocystis arieticanis (1/19 animals), whose known intermediate hosts are sheep. In addition, Sarcocystis capracanis , which is known to form sarcocysts in goats, was detected in two animals. The results of this study demonstrated the digestion method to be superior over the direct isolation of sarcocysts for the molecular identification of Sarcocystis species in a certain host. Future research of Sarcocystis diversity in wild ovine and caprine species is needed.